The role of textbooks in language learning (Ta'limning zamonaviy transformatsiyasi, 2024)
In this article, we describe language learning, its stages, andthe role of textbooks in the language learning process. As learning a new languageand improving knowledge is a requirement of the present time, the role of textbooksis incomparable.